INVESTIGATION OF FACTORS INFLUENCING ON RADIATION SITUATION FORMING DURING UTILIZATION OF NUCLEAR OBJECTS OF MARINE EQUIPMENT - A. V. Ivanchenko; S. V. Natkha; A. A. Shayakhmetova; D. V. Arefieva (Радиационная гигиена)
The article contains the results of the radiation situation investigation during fulfilling operations of utilization of nuclear objects of marine equipment in the facilities of nuclear shipbuilding and ship repair of Murmansk and Archangelsk regions. The results of research had reviled main radiation indices, which determine the facilities staff working conditions. During the cutting of constructions of nuclear objects of marine equipment the levels of radioactive contamination of the surfaces and aerosols volumetric activity in a whole do not exceed permissible levels set in RSS-99/2009 and depend on the types of operations fulfilling in the utilized object. The determining radiation factor for classifying of working conditions in the facilities is the equivalent dose rate of gamma-exposure the values of which are in the range of 0.5 – 8700.0 μSv/h.